Integration of Artificial Intelligence in Completing Final Projects as a Form of Student Independence and Creativity - Wibowo, Adi; Faridah, Ida (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research explores the role of artificial intelligence (AI) integration in increasing student independence and creativity while completing the final project in higher education. This research is based on technological advances in artificial intelligence used by students in their final projects as a form of creativity and student independence. This study uses a qualitative approach with a multi-case case study design in two Islamic religious universities. Data was collected through in-depth interviews with several lecturers and students and top management as informants, observations, and documentation analysis, which were then analyzed using data reduction techniques and inductive conclusions drawn. The main findings of this study reveal that the application of AI in final projects not only speeds up the completion process but also stimulates students' creativity through advanced analytical tools that allow them to explore innovative solutions to complex problems. In addition, AI will enable students to develop research independence and encourage them to think critically and adaptively to technological changes in an academic context. The research findings as a practical contribution show that integrating AI in the curriculum and final projects can enrich the learning process, broaden academic horizons, and improve students' readiness to face rapidly evolving industry challenges.